From Food Gathering to Horticulture: The Food Getting Techniques of Shompen of Great Nicobar Island. Issue 1 (June 2020) - Sasikumar, M.
Abstract: Classical social evolutionists generally assumed that the transformation of human societies from one particular mode of production to another is an evolutionary progression. It is a passage from hunting–gathering to herding and cultivation as alternative strategies to exploit a 'given' environment. This article portrays the strategies adopted by the Shompen to expand and ensure optimal diet throughout the year. The local environmental conditions and the state of technology the community has achieved had its bearing upon determining the nature of adaptive strategy evolved. The Shompen unlike their counterparts in the Andaman Islands have developed a multipronged strategy to survive at a distant, remote and inaccessible habitat in a largely isolated island that too through independent innovation of certain technologies. In this article, an attempt has been made to establish that the progression of societies was not always linear as assumed by the classical social evolutionists.